The Research Progress on Intestinal Stem Cells and Its Relationship with Intestinal Microbiota - Hou, Qihang; Ye, Lulu; Huang, Lulu; Yu, Qinghua (Frontiers in Immunology, 2017)
The intestine is home to trillions of microorganisms, and the vast diversity within this gut microbiota exists in a balanced state to protect the intestinal mucosal barrier. Research into the association of the intestinal microbiota with health and disease (including diet, nutrition, obesity, inflammatory bowel disease and cancer) continues to expand, with the field advancing at a rapid rate. Intestinal stem cells (ISCs) are the fundamental component of the mucosal barrier; they undergo continuous proliferation to replace the epithelium, which is also intimately involved in intestinal diseases. The intestinal microbiota, such as Lactobacillus, communicates with intestinal stem cells both directly and indirectly to regulate the proliferation and differentiation of ISCs. Moreover, Salmonella infection significantly decreased the expression of intestinal stem cell markers Lgr5 and Bmi1. However, the detailed interaction of intestinal microbiota and ISCs are still unclear. This review considers the progress of research on the model and niches of intestinal stem cells, as well as the complex interplay between the gut microbiota and ISCs, which will be crucial for explaining the mechanisms of intestinal diseases related to imbalances in the intestinal microbiota and ISCs.